2014
DOI: 10.5812/ircmj.13461
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Post-Traumatic Stress Disorder and Social Supports Among Parents of Premature and Full-Term Infants

Abstract: Background:Premature birth is one of the most important unresolved reproductive health problems. Premature birth is often traumatic and a source of distress for parents. Increased parental stress during the first year of their infant's life is a risk factor for later behavioral problems in infants.Objectives:This study was designed to compare anxiety, post-traumatic stress, and social supports in parents of premature and mature infants.Patients and Methods:This was a comparative descriptive study conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…The total score for each subscale of STAI is from 20 to 80. Higher scores represent higher anxiety in the individuals (18,19 (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…The total score for each subscale of STAI is from 20 to 80. Higher scores represent higher anxiety in the individuals (18,19 (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…Preterm birth refers to childbirth before 37 completed weeks and its frequency rate has been reported to be about 5 to 13% (1,2). Parents of preterm neonates are exposed to stress associated with their infant's survive and immaturity, neonatal hospitalization, parenting problems and financial burdens.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that about 1.5% -3% of parents of full term neonates have shown signs of PTSD after infants' birth (6). Both pregnancy and delivery are critical periods for parents which can induce large physiological, emotional, psychological and social changes (1). Different risk factors such as previous history of psychological problems and trauma, prenatal and obstetric complications, unwanted pregnancy, lack of familial and social supports and type of delivery contribute to the development of postpartum PTSD (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that the mothers of premature infants in the NICU may have a mild level (11,12), medium level (13,14) and high level (15,16) of anxiety.…”
Section: Introductionmentioning
confidence: 99%